(untitled) (Biological Sciences - PJSIR, 1998)
To economize the feeding expenditure, a mixture of filter cake (a sugar industry by-product) and cotton seed cake in addition to other feed ingredients, was fed to the young buffalo calves. In addition, the animals were fed on maize fodder in Kharif season (summer) and berseem in Rabi season (winter) ad-libitum. The duration of experiments varied from 121 to 150 days. In all the experiments, weight gained by the animals increased with increasing quantity of filter cake in the diet. The trend in weight gain due to treatments remained almost similar and filter cake containing diet gave higher weight gains over pure cotton seed cake. Weight gain(%) by animals receiving pure cotton seed cake varied from 18.1 to 24.7 %, whereas filter cake containing diets gave 20.6 to 37.7% weight gain.